Meme Symbolization in New Media as A Representation of Political Communication in The Digital Space - Humaini; Satyo, Nur (JILPR Journal Indonesia Law and Policy Review, 2024)
This research wants to see the meme symbol as a representation of political communication in the new media or digital space. What new media and digital space conveyed by Jurgen Habermas are used as public spaces, where users can interact and transact in new meida digital spaces. The presence of new media and digital space in the midst of society provides a variety of choices for the public to determine what information and messages will be carried out when the mass media is in front of them in their daily life. Therefore, this research focuses on a meme terminology. Memes in mass media and digital space are often found in various styles. But what's interesting is how memes themselves are contextualized in the context of political communication. Research using a qualitative approach is of course in the form of obtaining data and describing the data, according to field data